BANTUAN DESAIN GAPURA DENGAN IDENTITAS LOKAL PADA KELURAHAN SUKAJADI KECAMATAN TALANG KELAPA - Debby Sinta Devi; Fathoni Usman; Ratih Baniva; Sumi Amariena Hamim; Marguan Fauzi; Denie Chandra; Febryandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
This community service activity was carried out in Sukajadi Village, Talang Kelapa Subdistrict, Banyuasin Regency, with the aim of designing and planning a gate that could represent the local identity of the area. As an architectural element, the gate not only functions as an entrance, but also as a symbol of culture, history, and local wisdom values of the community. The main challenge faced by Sukajadi Village is the absence of a gate that represents the local identity and cultural character of the local community. Through a participatory approach, this activity involved the community, the subdistrict government, and academics in all stages of implementation, from field surveys, interviews with community leaders, focus group discussions, inventory of local potential, to technical design using AutoCAD and SketchUp software. The result of this activity was a modern minimalist gate design with a harmonious blue and cream color composition, complete with the government and university logos as symbols of collaboration. The total planned construction budget of IDR 17,106,814.00 was prepared transparently and agreed upon by all stakeholders. Based on the satisfaction survey results, 100% of respondents expressed satisfaction with the quality of the design and the collaborative process. This activity demonstrates that community service based on participation can strengthen local identity, increase community ownership, and serve as a model for collaboration between academics and residents in sustainable development based on local wisdom.